Antagonist co-activation during sit-to-stand in post stroke subjects - Cavaco, Jesica Andreina Ferreira (2021)
Antagonist co-activation is frequently altered in post-stroke subjects. To explore the changes in antagonist co-activation ratio in TA/GM, TA/SOL and RF/BF muscle pairs during the sub-phases of sit-to-stand functional task, in both contralesional and ipsilesional limbs, in post-stroke subjects. Eighteen subjects were instructed to sit-to-stand task. Surface eletromayography was recorded in tibialis anterior (TA), Soleus (SOL), gastrocnemius medialis (GM), rectus femoris (RF) and bíceps femoris (BF) muscles, bilaterally. Sit-to-stand movement was divided in three sub-phases (forrward translation, seat-off and antigravity with stabilization), during which anatagonist co-activation ratios were calculated for the muscle pairs TA/GM, TA/SOL and RF/BF. No significant diferences of the antagonista co-activation ratio were detected between both lower limbs. Statistical diferences were observed in the muscle pair TA/GM between forward translation and seat-off and between seat-off and antigravity with stabiliazation in contralesional limb (p<0,05) and in the RF/BF muscle pair between forward translation and seat-off bilaterally (p<0,05). Statistical diferences were observed between muscla pairs during sub-phases (p<0,05). Our findings demonstrate that, in post-stroke subjects, both lower limbs have na identical behaviour during sit-to-stand movement and seems to exist a variation of antagonista co-activation ratio between sub-phases and between muscle pairs.